INTEGRATED MANAGEMENT OF MANGROVES ECOSYSTEM IN LAMPUNG MANGROVE CENTER (LMC) EAST LAMPUNG REGENCY, INDONESIA - Asihing Kustanti; Bramasto Nugroho; Dudung Darusman; Cecep Kusmana (JOURNAL OF COASTAL DEVELOPMENT, 2012)
Mangroves forest ecosystem along the east coastal in Lampung Mangrove Center (LMC) Margasari Village is a renewable resources. It is a border between two ecosystem. Because of that situation, more than one stakeholders involved. There are department involues, Forestry Fisheries and Marine, and Agriculture Department in East Lampung District. Often, the policy of each department is not efficient and effective.  Based on that situation, on 2006, the mangroves management try to make an integrated model between the stakeholders.  In this research, It want to know the effectiveness of that model.  The samples in this research used Simple Random Sampling which they were 25 the people and the team of integrated management of University of Lampung and the East Lampung Regency government. The datas will be described and analysis with SWOT Analizing (Strength, Weakness, Opportunities, and Threats). The strategy of the integrated management will be defined after that.  Integrated management of mangroves ecosystem in Margasari Village have in good management of sustainability approach and increase the welfare of the people.  The position of the analzing of the integrated management is on the aggressive curve.  It is indicated that the integrated management has been done since 2006 have progressive development, between the people, government, and  University of Lampung. The strategies of management plan are education for the people on mangroves ecosystem functions and benefits, human resources development, law enforcement in break the rule in mangroves management (illegal loging and wild harvesting), development in international and national net working,  science and technology development, and  community empowerment and economyc increase.